2014
DOI: 10.1039/c3nr06722j
|View full text |Cite
|
Sign up to set email alerts
|

A simple model for understanding the fluorescence behavior of Au25 nanoclusters

Abstract: In this work, we synthesized Au25 nanoclusters protected by 2-(naphthalen-2-yl)ethanethiolate. Our experiments revealed that the luminescence of this nanocluster consists of two bands, namely, band I centered at 740 nm and band II centered at 680 nm. Compared with 2-phenylethanethiolate protected Au25 nanoclusters, this new nanocluster has a much higher QY (quantum yield) value (6.5 times higher). Fluorescence lifetime measurements showed multiple components, i.e. 0.15 ns, ∼20 ns and ∼150 ns. With an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Although some of the fractions were not atomically pure ( n < 15, n > 29) very interestingly these authors reported that, as shown in Table , independently on the size, the molar absorption coefficient is of the order of 10 4 m –1 cm –1 . The molar absorption spectrum of Au 25 (SC 2 H 4 Ph) 18 , reported more recently by Wang et al, confirmed these results …”
Section: Uv/vis Absorption Of Gncssupporting
confidence: 84%
“…Although some of the fractions were not atomically pure ( n < 15, n > 29) very interestingly these authors reported that, as shown in Table , independently on the size, the molar absorption coefficient is of the order of 10 4 m –1 cm –1 . The molar absorption spectrum of Au 25 (SC 2 H 4 Ph) 18 , reported more recently by Wang et al, confirmed these results …”
Section: Uv/vis Absorption Of Gncssupporting
confidence: 84%
“…[11][12][13][14] Since the size of metal nanoclusters is close to their Fermi wavelength (<1 nm), they behave like molecules. The fluorescence observed from dendrimer coated AuNCs follows the free electron model and arise from intraband (sp-sp) transitions, which are sensitive to the cluster sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work by Zhou's group has established that the ligand types protecting the thiolated Au 25 core are important because some ligands can enhance the quantum yield. 29 Moreover, the fluorescence mechanism in a thiolated gold cluster is not clear but there exist some important proposals. 30,31 Regarding chiroptical properties of silver-doped clusters, Jin's group reported that the thiolated Au 18 cluster is nonchiral because there exists a symmetry plane along the dimer motif.…”
Section: Bmentioning
confidence: 99%